Quo Vadis Hukum Pidana Islam dalam Sistem Hukum Pidana Indonesia - Ahmad Naufal Kawakib (UNIVERSITAS BONDOWOSO, 2022)
The Criminal Code used by the Unitary State of the Republic of Indonesia comes from the Criminal Code (KUHP), namely the Dutch Criminal Code with some modifications to its provisions, although there are several criminal provisions that apply in Indonesia which are regulated outside the Criminal Code. We often hear of efforts to amend the Criminal Code through the Criminal Code Bill, but this is still controversial in Indonesia. One of the inputs for improving the Draft Criminal Code is to adapt it to the development of community conditions and incorporate norms for social development and application, which are mostly sourced from religious values. In the Draft Criminal Code, in addition to codifying all criminal-related rules, it is hoped that it can further strengthen the existence of Islamic criminal law through the values ​​of justice, equality, and interests and benefits. Namely by understanding the concept of Qot'i and dhanny, whose values ​​are the essence of Islamic criminal law. Therefore, although the guidelines used in the Indonesian national legal system are positive legal regulations, they contain the essence of Islamic criminal law values.